Financial Infidelity in Blended Families: Determinants and Detriments - Mikel Van Cleve; Ashley McWhorter Keamo; Sonya Lutter; Jeremy B. Yorgason (Journal of Financial Therapy, 2024)
Blended families face unique challenges in managing finances, with issues like financial infidelity posing significant threats to family harmony. This exploratory study investigates the relationships between genetic relatedness, emotional fusion, and financial infidelity in blended families. Employing the Actor-Partner Interdependence Model (APIM) on data from the Couple Relationships and Transition Experiences (CREATE) dataset, results suggest that the presence of stepchildren is associated with an increased probability of financial infidelity among wives’ actor effects. Additionally, emotional fusion moderates the relationship between the presence of stepchildren and financial infidelity for husbands in both actor and partner effects and for wives in the partner effects. These findings emphasize the critical roles of effective communication and healthy family relationships in fostering financial transparency and trust within blended family structures and highlight the need for targeted interventions by practitioners.
Keywords: blended families; stepchildren; financial infidelity; family systems theory; kin selection theory; actor-partner interdependence model